Analysis of Online Buy-Sell Agreement on Market Place With Cash on Delivery System - Furqaansyah (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
The validity of online buying and selling transactions through a marketplace with a Cash on Delivery system is principally regulated in Article 1320 of the Civil Code which contains the terms of the validity of an agreement based on an agreement between the buyer and seller or marketplace. However, in practice there are still deficiencies in fulfilling the legal requirements of the agreement which results in a sale and purchase agreement with the Cash on Delivery system in online buying and selling transactions not fulfilling the validity of the agreement in positive law in Indonesia. The responsibility provided by the Shopee Indonesia website manager for losses suffered by consumers has been fully regulated through the provision of consumer reporting facilities for losses experienced by consumers, blocking negative content, providing Shopee Indonesia guarantees, refunds to consumers, following up on fake accounts. sellers, as well as protection of consumer personal and credit card data. However, in practice sellers and buyers who use the Shopee platform have not fully obtained their rights when they experience losses due to buying and selling online.